Effects of High-dose Vitamin E Supplementation on Markers of Cardiometabolic Risk and Oxidative Stress in Patients with Diabetic Nephropathy: a Randomized Double-blinded Controlled Trial (Iranian Journal of Kidney Diseases, 2018)
Introduction. Patients with diabetic nephropathy (DN) may benefit from vitamin E's antilipid and antioxidant activities. This study aimed to evaluate the effects of high-dose vitamin E supplementation on markers of cardiometabolic risk and oxidative stress in patients with DN. Materials and Methods. This randomized controlled trial was carried out on 54 patients with DN that were randomly divided into 2 groups to receive vitamin E supplement (800 IU/d) or placebo for 12 weeks. Fasting blood samples were obtained at baseline and after the 12-week intervention to determine markers of cardiometabolic risk and oxidative stress. Results. Vitamin E supplementation, compared with the placebo, resulted in a significant reduction in serum total cholesterol (-14.3 ± 29.9 mg/dL versus -0.8 ± 13.1 mg/L, P = .03), low-density lipoprotein cholesterol (-16.4 ± 28.5 mg/dL versus 0.1 ± 17.2 mg/L, P = .01), and ratio of total cholesterol to high-density lipoprotein cholesterol ratio (-0.5 ± 0.7 versus 0.1 ± 0.5, P = .001), and a significant elevation in vitamin E levels (39.7 ± 12.4 nmol/mL versus -0.5 ± 1.3 nmol/mL, P < .001) and high-density lipoprotein cholesterol levels (1.4 ± 3.7 versus -2.1 ± 5.1 mg/L, P = .006). It also resulted in a significant elevation in plasma glutathione levels. Conclusions. Our study demonstrated that high-dose vitamin E supplementation for 12 weeks had favorable effects on lipid profile and glutathione levels of patients with DN, except for triglycerides, very low-density lipoprotein cholesterol, nitric oxide, and total antioxidant capacity levels.